The direct health-care burden of valvular heart disease: evidence from US national survey data - Moore M; Chen J; Mallow PJ; Rizzo JA (Dove Medical Press, 2016)
Matt Moore,1 Jie Chen,2 Peter J Mallow,3 John A Rizzo4 1Global Health Economic Strategy, Edwards Lifesciences Inc, Irvine, CA, 2Department of Health Services and Administration, University of Maryland, College Park, MD, 3Health Economics and Outcomes Research, CTI Clinical Trial & Consulting Services Inc, Cincinnati, OH, 4Department of Preventive Medicine and Economics, Stony Brook University, Stony Brook, NY, USA Purpose: This study quantified the overall effects of aortic valve disease (AVD) and mitral valve disease (MVD) by disease severity on direct health-care costs to insurers and patients.Materials and methods: Based on 1996–2011 data from the Medical Expenditure Panel Survey (MEPS), a large, nationally representative US database, multivariate analyses were performed to assess the relationship between AVD and MVD and direct annual health-care costs to insurers and patients, at individual and US-aggregate levels. Adults aged 18 years and over with diagnosis codes for AVD or MVD based on International Classification of Diseases (ninth revision) diagnosis codes were identified. Subjects were further classified as symptomatic AVD, asymptomatic AVD, symptomatic MVD, and asymptomatic MVD. These classifications were determined with clinical assistance and based in part on data availability in the MEPS.Results: The MEPS database included 148 patients with AVD: 53 patients with symptomatic AVD, 95 patients with asymptomatic AVD, and 1,051 with MVD, including 315 patients with symptomatic MVD and 736 patients with asymptomatic MVD. Symptomatic AVD had the largest incremental effect on annual per patient health-care expenditure: $12,789 for symptomatic AVD, $10,816 for asymptomatic AVD, $5,163 for symptomatic MVD, and $1,755 for asymptomatic MVD. When aggregated to the US population, heart-valve disease accounted for an incremental annual cost of $23.4 billion. The largest aggregate annual costs were incurred by patients with symptomatic MVD ($7.6 billion), followed by symptomatic AVD ($5.6 billion), asymptomatic MVD ($5.6 billion), and asymptomatic AVD ($4.6 billion).Conclusion: The annualized incremental costs of heart-valve disease were substantial for all groups examined, and greatest for patients with symptomatic MVD. This reflects the relatively high prevalence associated with this group. With a growing and aging population, the prevalence of heart-valve disease is expected to rise, increasing the burden on public health. Keywords: aortic valve disease, mitral valve disease, direct health-care costs, Medical Expenditure Panel Survey